2016
DOI: 10.1099/jgv.0.000444
|View full text |Cite
|
Sign up to set email alerts
|

The significance of naturally occurring neuraminidase quasispecies of H5N1 avian influenza virus on resistance to oseltamivir: a point of concern

Abstract: Viral adaptability and survival arise due to the presence of quasispecies populations that are able to escape the immune response or produce drug-resistant variants. However, the presence of H5N1 virus with natural mutations acquired without any drug selection pressure poses a great threat. Cloacal samples collected from the 2004-2005 epidemics in Thailand from Asian open-billed storks revealed one major and several minor quasispecies populations with mutations on the oseltamivir (OTV)-binding site of the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…High level of resistance (up to 91%) to M2 blockers has been reported in H3N2 virus strain in American isolates ( 6 ). Resistance has also been reported in H5N1 virus ( 7 ). IAV resistance to NA inhibitors has also become an increasingly prevalent concern, with the recent highly fatal outbreak of influenza A(H1N1)pdm09 in India 2015 associated with oseltamivir drug resistance ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 84%
“…High level of resistance (up to 91%) to M2 blockers has been reported in H3N2 virus strain in American isolates ( 6 ). Resistance has also been reported in H5N1 virus ( 7 ). IAV resistance to NA inhibitors has also become an increasingly prevalent concern, with the recent highly fatal outbreak of influenza A(H1N1)pdm09 in India 2015 associated with oseltamivir drug resistance ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 84%
“…Digestion activity was plotted as a function of inhibitor concentration by quantifying the intensity of the digested bands with ImageJ software. The IC 50 values were calculated as in our work on endonuclease inhibition [8]. The intensity of λ-DNA bands was subtracted from negative control (λ-DNA lane) and then normalized from the positive control (λ-DNA and PA protein lane without inhibitor).…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, we demonstrated that large flexible para-sulfonato-calix[n]arenes could inhibit in vitro H3N2 PA endonuclease. Combining the methodology of experimental inhibition studies and theoretical docking work has given us insights on the mechanism of endonuclease inhibition by para-sulfonato-calix [8]arene. The larger SC8a anion can bind to the K34, Y130, K134, and K137 residues of the DNA binding pharmacophore pocket and also interact at the catalytic site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations